In harm's way: the memoir of a child protection lawyer - Thornhill, Teresa (HaperCollinsPublishers, 2024)
When the system fails the parents, how can it protect the children? Welcome to the secretive world of the Family Court. What's it like to act for a father who has recently overcome his drug problem but risks losing his beloved son to foster care?'? Or to represent a young mother whose abusive childhood has left her depressed and struggling to cope, to the point where the local authority is seeking to persuade the Family Court to place her small children for adoption? In this hard-hitting account of her work representing parents in care proceedings in the Family Court, child protection lawyer Teresa Thornhill conveys the dilemmas inherent in the job and shows how our under-resourced system of child protection in both its social work and legal aspects often fails to provide support that could enable the most vulnerable parents to continue to care for their children